PECULIARITIES OF THE COURSEOF CORONARY HEART DISEASE IN PATIENTS WITH DIABETES MELLITUS 2 TYPE - Sodiqova, N.G.; Djafarova, N.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The article presents summary data on the course of ischemic heart disease in patients with type 2 diabetes, as well as schemes of changes occurring in the heart of a patient with diabetes and the development of unstable atherosclerotic plaque in the given pathology.